Model Resiliensi terhadap Stres: Tinjauan Literatur atas Faktor Protektif dan Mekanisme Adaptif - Bachtiar Safrudin; Rachma Octavianti; Salsabila Sarda; Vinda Yanti Anggun Sari; Nanda Imuttyah; Rahmah Dani; Amanda Putri; Yunita Yunita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This research examines various aspects of stress and resilience in individuals and families in the contexts of mental health, education, and work environment through psychosocial interventions and theoretical frameworks of adaptation. The Current Experience Scale (CES) resilience measurement model developed alongside the Relaxation Response Resiliency Program (SMART-3RP) intervention demonstrates effectiveness in enhancing adaptive capacity to chronic stress and psychometric validity of the measure. Interventions involving deep breathing relaxation and dhikr using the Roy Adaptation Model approach significantly reduce anxiety in elderly hypertensive patients through neuroendocrine stimulation that activates calming hormones. Other studies affirm the role of optimism and self-adjustment as protective factors reducing academic stress in students during online learning and highlight the efficacy of resilience training based on relaxation and cognitive-behavioral techniques in academic stress management. The Family Resilience Enhancement Program (FREP) has been proven to improve the quality of life for families with special needs children by strengthening family resources and offering counseling guidance. Adaptation and validation of the Parental Stress Scale in Indonesia identify two main dimensions of parental stress fitting the collectivist cultural context. Work environment and personal characteristics significantly influence employee work stress, where adaptive ability serves as a crucial moderator mitigating negative stress impacts. The Stuart stress adaptation model emphasizes the importance of coping mechanisms and holistic adaptive responses in psychiatric nursing care. These findings underline the essential role of adaptation and resilience interventions across different fields to enhance mental health, psychological well-being, and adaptive functioning of individuals and families.